2016
DOI: 10.1080/03630242.2016.1164273
|View full text |Cite
|
Sign up to set email alerts
|

Impact of occupation on stress and anxiety among Indian women

Abstract: The objectives of this study were to: (1) assess the prevalence of anxiety and stress in Indian women; and (2) evaluate the relationship of occupation to the prevalence of anxiety and stress. A cross-sectional study was performed from January 2013 to June 2014, on women (aged 18-50 years) randomly selected from different occupations in Gujarat, India. Anxiety was evaluated using Spielberg's State and Trait Anxiety Inventory scale and stress was assessed using the International Stress Management Association que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…A similar study done among Gujarati women belonging to the urban/semi-urban area has found the prevalence of anxiety and stress to be 35% and 26%, respectively which is alarmingly high when compared with our estimates. 17 The difference in prevalence estimates between the two aforementioned studies can be attributed to the existing differences in the study setting, with a former study from a rural setting, when compared with the latter one from an urban area. It is observed that among 45 women who reported depressive symptoms, 15 (35.6%) and 10 (22.2%) had concomitant anxiety and stress.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study done among Gujarati women belonging to the urban/semi-urban area has found the prevalence of anxiety and stress to be 35% and 26%, respectively which is alarmingly high when compared with our estimates. 17 The difference in prevalence estimates between the two aforementioned studies can be attributed to the existing differences in the study setting, with a former study from a rural setting, when compared with the latter one from an urban area. It is observed that among 45 women who reported depressive symptoms, 15 (35.6%) and 10 (22.2%) had concomitant anxiety and stress.…”
Section: Discussionmentioning
confidence: 99%
“…have reported a 40% prevalence of anxiety in homemakers, which was 1.2 times the anxiety in working women. [ 10 ] The variance may be due to the different scale used in their study. A community-based prevalence study, using the GAD-7 scale, conducted in Sweden by Johansson et al .…”
Section: Discussionmentioning
confidence: 99%
“…[7] in two large community samples in a developing country and Pinal Patel et al . [8] in Gujarat, respectively. Data on depression are being analyzed and will be published later.…”
Section: Methodsmentioning
confidence: 99%